Microstructural and Mechanical Characterization of Aluminum Matrix Composites Produced by Laser Powder Bed Fusion1 . Issue 11 (17th May 2017) - Aversa, Alberta; Marchese, Giulio; Lorusso, Massimo; Calignano, Flaviana; Biamino, Sara; Ambrosio, Elisa P.; Manfredi, Diego; Fino, Paolo; Lombardi, Mariangela; Pavese, Matteo
Abstract : Laser powder bed fusion is one of the most widely used additive manufacturing process owing to its ability to produce functional near net shape metal components. This paper focuses on the microstructural and mechanical characterization of four aluminum matrix composites produced by laser powder bed fusion using AlSi10Mg as matrix with four different ceramic particles. On the basis of the building parameters, composites present specific microstructural features able to influence the strengthening mechanisms and, consequently, their mechanical and thermal properties. It is demonstrated that, in order to obtain dense materials, in composite processing, it is indispensable to use energy densities which are higher than that of the matrix. This change in process parameters probably implies a different heat profile in the part during the building process, with a consequent increase in cell size and decrease in yield strength of the MMCs with respect to the pure aluminum. Abstract : This work investigates the feasibility and the properties of AlSi10Mg matrix composites produced by laser powder bed fusion. It is clarified that high energy densities are required in order to obtain dense composites. The building parameters strongly influence composite microstructures, with evident consequences on their mechanical properties.